Ethnomedicine of the Kagera Region, north western Tanzania. Part 2: The medicinal plants used in Katoro Ward, Bukoba District - Mbabazi Pamela K; Otieno Donald F; Moshi Mainen J; Weisheit Anke (BMC, 2010)
Abstract Background The Kagera region of north western Tanzania has a rich culture of traditional medicine use and practices. The dynamic inter-ethnic interactions of different people from the surrounding countries constitute a rich reservoir of herbal based healing practices. This study, the second on an ongoing series, reports on the medicinal plant species used in Katoro ward, Bukoba District, and tries to use the literature to establish proof of the therapeutic claims. Methodology Ethnomedical information was collected using Semi-structured interviews in Kyamlaile and Kashaba villages of Katoro, and in roadside bushes on the way from Katoro to Bukoba through Kyaka. Data collected included the common/local names of the plants, parts used, the diseases treated, methods of preparation, dosage, frequency and duration of treatments. Information on toxicity and antidote were also collected. Literature was consulted to get corroborative information on similar ethnomedical claims and proven biological activities of the plants. Results Thirty three (33) plant species for treatement of 13 different disease categories were documented. The most frequently treated diseases were those categorized as specific diseases/conditions (23.8% of all remedies) while eye diseases were the least treated using medicinal plants (1.5% of all remedies). Literature reports support 47% of the claims including proven anti-malarial, anti-microbial and anti-inflammatory activity or similar ethnomedical uses. Leaves were the most frequently used plant part (20 species) followed by roots (13 species) while making of decoctions, pounding, squeezing, making infusions, burning and grinding to powder were the most common methods used to prepare a majority of the therapies. Conclusion Therapeutic claims made on plants used in traditional medicine in Katoro ward of Bukoba district are well supported by literature, with 47% of the claims having already been reported. This study further enhances the validity of plants used in traditional medicine in this region as resources that can be relied on to provide effective, accessible and affordable basic healthcare to the local communities. The plants documented also have the potential of being used in drug development and on farm domestication initiatives.